PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN “MATHOPOLY CHALLENGE” TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS V SDN KARANGSARI - Khairullah, Afif Dzaky; Syamila, Munadia; Yuniastri, Kartika; Kurozi, Kenvi Amin Nata; Novianto, Anwar (De Fermat : Jurnal Pendidikan Matematika, 2026)
Mathematics is a crucial subject in elementary education that shapes students’ critical thinking and problem-solving skills. However, observations in grade V of SDN Karangsari show that students still struggle with the concept of dividing two-digit numbers, compounded by a lack of varied learning media. This study aims to examine the effect of using the Mathopoly Challenge learning media on students’ mathematics learning outcomes. A quantitative approach with a One Group Pretest-Posttest Design experimental method was applied, involving all 10 fifth-grade students of SDN Karangsari. Data were collected through observation, interviews, and pretest-posttest assessments, then analyzed using the Wilcoxon Signed Rank Test and N-Gain calculation. The results showed a significant improvement in students’ learning outcomes, with the average pretest score of 61.33 increasing to 74.67 in the posttest, a significance value of p = 0.006 (< 0.05), and an average N-Gain of 0.37 in the medium category. These findings indicate that Mathopoly Challenge is effective in improving students’ mathematics learning outcomes of division concepts.